Non-financial disclosure and integrated reporting : practices and critical issues - Songini, Lucrezia; Pistoni, Anna; Baret, Pierre; Kunc, Martin (Bingley, U.K. : Emerald Publishing Limited, 2020)
The financial crisis of 2008 and its economic and social aftermath have highlighted the limits and risks of an increasingly global and embedded economy. Weakening society's trust in organizations and institutions, this has led to calls for new strategic paradigms that focus more on the ethical conduct of organizations. Performance measurement for sustainability and corporate social responsibility (CSR) plays a central role in these new contexts. The landscape of performance measurement and reporting is changing quickly, with calls for more integrated reporting and compulsory non-financial disclosures. Keeping up with those changes is a significant concern of managers in many organizations. Including research on the effectiveness and quality of non-financial disclosure, CSR/sustainability disclosure and Integrated Reporting, this exciting new volume looks to bridge the gaps in environmental, social and financial performance so managers can understand and successfully implement a broader, integrated view of performance measurement and reporting. Aimed at researchers and managers interested in performance measurement, this volume includes innovative research that sheds light on topics such as the determinants of disclosure quality, the identification of appropriate metrics, the relationship among the different disclosure mechanisms and between voluntary and mandatory disclosure, and many more.
Introduction : Non-financial disclosure and integrated reporting : practices and critical issues -- Part 1: Key issues and practices in non-financial performance measurement -- 1. Desperately seeking a standard metric for corporate social performance / Marco Masip -- 2. Evolution of non-financial reporting in France : the innovative adaptation of a cognac producer / Pierre Baret and Vincent Helfrich -- 3. The effect of mandatory publication of nonfinancial disclosure in Europe on sustainability reporting quality : first insights about Italian and German companies / Giorgio Mion and Cristian R. Loza Adaui -- Part 2: Key issues and practices in integrated reporting -- 4. Mapping circular economy processes in integrated reporting: a dynamic resource-based approach / Martin Kunc, Federico Barnabè, and Maria Cleofe Giorgino -- 5. Integrated reporting and social disclosure: true love or forced marriage? A multidimensional analysis of a contested concept / Sergio Paternostro -- 6. Tone at top in integrated reporting : the role of non-financial performance / Valentina Beretta, Maria Chiara De Martini, and Sara Trucco -- 7. Integrated reporting quality: an analysis of key determinants / Lucrezia Songini, Anna Pistoni, Francesco Bavagnoli, and Valentina Minutiello -- Conclusion.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Performance standards; Social responsibility of business; Business ethics; Global Financial Crisis, 2008-2009 -- Social aspects; Business & Economics -- General; Business ethics & social responsibility